Application of "retention coefficiency" method in shale gas resource evaluation: a case study of Upper Ordovician Wufeng Formation to Lower Silurian Longmaxi Formation, southeastern Sichuan Basin - Zhenxiang SONG; Baohua WANG; Xiangfeng WEI; Zhongliang MA (Shiyou shiyan dizhi, 2022)
Besides providing resulting data, the evaluation of resource abundance is more important to provide evidence for the optimization of favorable areas and the deployment of exploration. In view of the drawbacks of traditional methods, combined with the newly developed thermal-pressure simulation method of formation porosity and basin simulation method, this paper puts forward the process of shale gas resource evaluation using the "retention coefficiency" method. It is pointed out that the model of hydrocarbon generation-expulsion-retention and the "retention coefficiency"are the two most critical parameters in this new method. The Upper Ordovician Wufeng Formation to Lower Silurian Longmaxi Formation, which are the most highly explored shale in China, are taken as targets to illustrate the application process of the new method. Results show that the new method has good applicability and feasibility in shale gas resource evaluation. Compared with traditional methods, the "retention coefficiency" method not only considers the dynamic evolution process of shale gas, but also considers the influence of late preservation conditions on shale gas enrichment. In addition, the new method can describe the spatial distribution characteristics of shale gas resources, with a broad application prospect in shale gas resource evaluation and favorable area optimization.